Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I just derived it by using the generation function to first get raw moments. The result is


It was merely brutal force calculation, nothing interesting. So I was wondering, if there any one knows tricks that could simplify the process a bit.

share|cite|improve this question
When the probability mass function involves factorials in the denominator (as in binomial and Poisson pmf), it is often easier to find $E[X(X-1)(X-2)(X-3)]$ rather than $E[X^4]$ etc. Of course, using the moment generating function (if you know what it is) is even easier. – Dilip Sarwate May 8 '12 at 1:11
up vote 5 down vote accepted

Let $X$ be binomial with $n$ trials and success probability $p$. I assume by fourth central moment you mean $E[(X - np)^4]$. Write $X = \sum_{i = 1} ^ n X_i$ where the $X_i$ are iid Bernoulli with success probability $p$. Then we want $$E\left[\left(\sum_{i = 1} ^ n (X_i - p)\right)^4 \right] = E\left[\sum_{1 \le i, j, k, l \le n} (X_i - p)(X_j - p)(X_k - p)(X_l - p) \right] = \sum_{1 \le i, j, k, l \le n}E[(X_i - p)(X_j - p)(X_k - p)(X_l - p)]$$ which effectively turns this into a counting problem. The terms in the sum on the right hand side are $0$ unless either $i = j = k = l$, which happens $n$ times, or when there are two pairs of matching indicies, which happens $\binom n 2 \binom 4 2 = 3n(n - 1)$ times. This gives us $$E[(X - np)^4] = n\mu_4 + 3n(n - 1)\sigma^4 \tag{$\dagger$}$$ as the fourth central moment, when $\sigma^2 = p(1 - p)$ is the variance $X_1$ and $\mu_4 = p(1 - p)^4 + p^4 (1 - p)$ is the fourth central moment of $X_1$. Note that in deriving ($\dagger$) we actually derived a general formula for the fourth central moment of a sum of iid random variables.

share|cite|improve this answer
+1 I was going exactly this way. – leonbloy May 8 '12 at 1:31
It's strange, I did these exact same calculations on a completely unrelated problem. I could almost copy and paste this answer from there. – guy May 8 '12 at 1:48
@guy at this point you should tell us what this problem was! – Immanuel Weihnacht Mar 23 at 17:05

An alternative approach would be to use cumulants. The fourth central moment of a random variable $X$ can be expressed in terms of cumulants as follows: $$\mu_4(X)=\kappa_4(X)+3\kappa^2_2(X).$$

Now, cumulants add over independent random variables and the second cumulant is just the variance, i.e., $\kappa_2=\mu_2$.

Writing $Y=\sum_{i=1}^n Z_i$, where the $Z_i\,$s are i.i.d. random variables, we have

\begin{eqnarray*} \mu_4(Y)&=&\kappa_4(Y)+3\kappa^2_2(Y)\\ &=&n\kappa_4(Z)+3[n\kappa_2(Z)]^2\\ &=&n\left[\mu_4(Z)-3\kappa_2^2(Z)\right]+3[n\kappa_2(Z)]^2\\ &=&n\, \mu_4(Z) +3n(n-1)\,\mu_2^2(Z). \end{eqnarray*}

share|cite|improve this answer

If you decide to pursue Dilips' strategy: For $k\geq 0$, define $$m_k=E\!\left[{X\choose k}\right]=\sum_{x\geq 0} {x\choose k} {n\choose x} p^x (1-p)^{n-x}.$$

We may not know what these numbers are, but we do know that \begin{eqnarray*} \sum_{k\geq0} m_k y^k &=& \sum_{k\geq0} \sum_{x\geq 0} {x\choose k} {n\choose x} p^x (1-p)^{n-x} y^k \\[5pt] & =& \sum_{x\geq 0} (1+y)^x {n\choose x} p^x (1-p)^{n-x}\\[5pt] &=& (py+1)^n. \end{eqnarray*}

Extracting the coefficient of $y^k$ on both sides gives $$m_k=E\!\left[{X\choose k}\right]= {n\choose k} p^k.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.